2014
DOI: 10.1111/1462-2920.12595
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ether lipids and composition of the archaeal community in terrestrial geothermal springs: impact of environmental variables

Abstract: Archaea can respond to changes in the environment by altering the composition of their membrane lipids, for example, by modification of the abundance and composition of glycerol dialkyl glycerol tetraethers (GDGTs). Here, we investigated the abundance and proportions of polar GDGTs (P-GDGTs) and core GDGTs (C-GDGTs) sampled in different seasons from Tengchong hot springs (Yunnan, China), which encompassed a pH range of 2.5-10.1 and a temperature range of 43.7-93.6°C. The phylogenetic composition of the archaea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 71 publications
(123 reference statements)
7
26
0
Order By: Relevance
“…Clustering of samples by archaeal community composition was performed using the base program in R 2.12.1. The relative abundance of archaeal phylotypes based on 16S rRNA gene sequences was imported into R and the distance matrix was computed with the squared Euclidean distance using the two-way joining method (Xie et al, 2014a). A hierarchical clustering tree was generated by the Heatmap command in R (Maindonald, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Clustering of samples by archaeal community composition was performed using the base program in R 2.12.1. The relative abundance of archaeal phylotypes based on 16S rRNA gene sequences was imported into R and the distance matrix was computed with the squared Euclidean distance using the two-way joining method (Xie et al, 2014a). A hierarchical clustering tree was generated by the Heatmap command in R (Maindonald, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…, ; Xie et al . ), which is thought to reduce the influx of protons in acidic environments (López de Saro et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of GDGT cyclopentane rings correlates inversely with pH (e.g. Macalady et al 2004;Pearson et al 2008;Boyd et al 2011Boyd et al , 2013Xie et al 2015), which is thought to reduce the influx of protons in acidic environments (L opez de Saro et al 2015). Therefore, as a study premise, we postulate that modifications to lipid membrane conformation required under different pH conditions necessitates adaptations in membrane localized proteins, including ammonia monooxygenase, to maintain essential protein functions and protein-protein interactions, along with normal protein folding.…”
Section: Introductionmentioning
confidence: 99%
“…Other environmental investigations have also demonstrated that the resident Archaea in terrestrial hot springs effect change in the packing density of their membranes in response to low pH, by increasing the cyclopentyl rings in GDGTs at the rank of community (Boyd et al, 2013;Xie et al, 2014a).…”
Section: Possible Mechanisms For Ti-ph Relationshipmentioning
confidence: 96%
“…This approach has, however, been used to study archaeal and bacterial biogeochemical process in hot springs Xie et al, 2014a). The aim of this study, therefore, was to examine on one hand temporal variation in core ether lipids and archaeal communities and, on the other hand, how they respond to seasonal changes in environmental conditions at a subtropical soil site.…”
Section: Introductionmentioning
confidence: 99%